Ehrlichiosis-Associated Hemophagocytic Lymphohistiocytosis: A Case Series and Review of the Literature - Hammoud, Kassem; Fulmer, Robert; Hamner, Megan; El Atrouni, Wissam (Case Reports in Hematology, 2023)
Background. Human monocytic ehrlichiosis (HME) is a potentially life-threatening tick-borne illness. HME-associated hemophagocytic lymphohistiocytosis (HLH) is a rare entity with a paucity of published literature regarding treatment and outcome. We present the clinical features, treatment, and outcomes of 4 patients at our institutions with HME-associated HLH. This review also summarizes the current literature regarding the presentation, treatment, and outcome of this infection-related HLH. Methods. We searched the PubMed database for case reports and case series. All cases were diagnosed according to the HLH-04 criteria. Results. Four cases of HME-associated HLH were included from our institutions. The literature review yielded 30 additional cases. About 41% of the cases were in the pediatric population; 59% were female; and all patients had fever, cytopenia, and elevated ferritin. Most patients were immunocompetent; all but one patient with available data were treated with doxycycline, and eight of the patients with available data received the HLH-94 treatment protocol. The mortality rate was 17.6%. Conclusions. HME-associated HLH is a rare but serious syndrome with significant mortality. Early treatment with doxycycline is critical, but the role of immunosuppressive therapy is individualized.